Effective Design and Visual Aids - Sakinah Sakinah; Dita Kurnia Sari Sembiring; Suhairi Suhairi (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2021)
The actualization of visual communication can’t be separated from bussines and aesthetic design. The sense is important role in creation. If it doesn’t, it will be treatise tragedy. The product of visual communication can’t be separated from media, as a mediation place among product, services, even self actualization with social community who became target. The presence of sense on every element in the design will frame the concept of design. Research methods uses a qualitative approach with emphasis on observation and documentation. The analize data uses case study. Creating with sense is appreciation problems, because every action of human involve all five senses. The appreciation through the imagination manifested visually may experience stylized, distortion, and adaptation. But interestingly, designer is able to capture the essence, so the sense be more involved in the creation process. The sense of design is the result of the appreciation that includes creative activity. The creative, expression, perception, character, productive, inventive, innovation, inspiration, and emergentif aspects that present in the overall design concept focused on achieving aesthetic value. The design of visual communications show the sense of the process until the final design. The sense of design is present in every element of the design such as illustration, typography, color, and layout.